Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1002/art.1780271209
|View full text |Cite
|
Sign up to set email alerts
|

Studies of anti‐f(ab')2 antibodies and possible immunologic control mechanisms in systemic lupus erythematosus

Abstract: Studies of anti‐DNA and anti‐F(ab')2 antibodies were performed by enzyme‐linked immunosorbent assay in 51 patients with systemic lupus erythematosus (SLE). Patients with severe, uncontrolled disease showed high levels of anti‐DNA and low levels of anti‐F(ab')2 antibodies. Patients with quiescent SLE usually showed high levels of anti‐F(ab')2 and low levels of anti‐DNA antibodies. Isolated anti‐F(ab')2 antibodies from autologous SLE remission serum or from the sera of unaffected siblings of SLE patients showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…The preliminary ELISA included analysis of both anti-DNA and anti-F(ab')i levels by using previously described methods [24,25], Binefly. microtitre plates were separately coated with 1 ^g/mlofcalfthymusdsDNAand 5//g/mlof purified F(ab'); fragment obtained from pepsin-digested human IgG (Cohn fraction II).…”
Section: Antigens and Elisa Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preliminary ELISA included analysis of both anti-DNA and anti-F(ab')i levels by using previously described methods [24,25], Binefly. microtitre plates were separately coated with 1 ^g/mlofcalfthymusdsDNAand 5//g/mlof purified F(ab'); fragment obtained from pepsin-digested human IgG (Cohn fraction II).…”
Section: Antigens and Elisa Testsmentioning
confidence: 99%
“…Thus, 70 mg of each IVIG lot were first absorbed with DNA-Sepharose to remove any possible anti-DNA activity [24]. and then passed over a column of DNA-absorbed IgG (derived from Cohn fraetion II) by using a recycling pump in order to deplete both anti-F(ab')2 and anti-Fc reactivities.…”
Section: Immunoabsorption Experinientsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In this area, reduction in titer of such negative regulatory molecules could have a stimulatory effect of anti-dsDNA antibody production. Indeed Silvestris et al 11 have found an inverse relationship between anti Fab 2 (which contain antibody to anti-dsDNA) and antidsDNA titers suggesting a regulatory role for the antiidiotypes to anti-dsDNA antibodies.…”
mentioning
confidence: 98%
“…Alternatively, epitopic peptides of these surrogate molecules, administered in soluble form, could induce speci®c tolerance and have an inhibitory effect on anti-dsDNA production. Also in the inhibitory class would be anti-idiotypes for anti-dsDNA, which have been shown to exist in normal individuals 11 and in certain lupus patients who produce anti-LaaSSB, anti-RoaSSA andaor anti-U 1 RNP, subsets of which have anti-idiotype speci®-city for anti-dsDNA molecules. 12 In this area, reduction in titer of such negative regulatory molecules could have a stimulatory effect of anti-dsDNA antibody production.…”
mentioning
confidence: 99%